The difference in effects of electric current pulses on inoculation of austenite and M7C3 carbides - Baoyu Geng; Rongfeng Zhou; Yongkun Li; Quiping Wang; Yehua Jiang (Materials Research Express, 2020)
It is a controversial issue whether the electric current pulse (ECP) has an inoculation effect on the solidification process. Two different high chromium cast irons were modified with the ECP above the freezing point temperature to investigate this issue. According to the statistical results of the number and size of primary phase grains, it was found that the ECP did not have an inoculation effect on the hypoeutectic high chromium cast irons (HOHCCI) whose primary phase was austenite. However, it had a significant inoculation effect on the hypereutectic high chromium cast irons (HEHCCI) whose primary phase was M7C3 carbides. The result indicates that the response of different primary phases to the ECP inoculation effect was different. The cause of the phenomenon is further analyzed by simulating the diffusion of atoms in the melt and comparing the binding forces of atomic clusters. The analysis shows that although the ECP can increase the number of atomic clusters (composition close to the primary phase) in the melt, the number of clusters retained to the nucleation temperature after the ECP removal is different because the binding forces of clusters in two melt is different.